Implementasi Kebijakan Sistem Administrasi Manunggal Satu Atap di Kabupaten Mandailing Natal - Abdul Kadir; Abdullah Afifuddin Lubis; Isnaini Isnaini (Universitas Negeri Medan, 2019)
Management of collection and management of motorized vehicle taxation is carried out in one office involving several related elements in its management. Motor vehicle tax collection carried out in one office is known as SAMSAT (One Roof Single Administration System), in which there is cooperation between the Indonesian National Police (POLRI) which has the function and authority in the field of registration and identification of motorized vehicles, Local Government in this case the Regional Tax and Retribution Management Agency in the field of motor vehicle tax collection (BBN-KB), PT. Jasa Raharja (Persero) which is authorized in the field of delivery of Road Traffic Accident Donations (SWDKLLJ). The results of this study indicate that the implementation of a one-stop single administration system in managing motor vehicle tax at the SAMSAT office in Mandailing Natal Regency viewed from the aspect of organizational structure, resources, communication and disposition in general has been good. In order to create professional services and satisfy SAMSAT taxpayers, Mandailing Natal District needs to conduct regular / regular coordination meetings so that periodic evaluations can also be carried out to make improvements to services provided from time to time.